2021
DOI: 10.1558/cis.20053
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tawhidi Worldview in Islamic World

Abstract: Modernization and the concomitant changes in people behavior are now blamed for the deterioration of the environment. This article points up desacralization of knowledge and the demise of esoteric tradition that followed to have an ecological impact in the Islamic world as the Muslims began to hold the bifurcated notion of “this-worldly” and “heavenly” in a completely distinct manner. Through modern education, Muslims adopted the notion of “independent existence” according to which nature exists in and of itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Against this ethical dilemma, a reconciling and reuniting worldview is needed. Toward this end, I humbly propose the Tawhidi (unitive) worldview explicated in my recent work on Islamic mysticism (Alkatiri 2021a). 6 It is a set of assumptions about the world that have powerful effects on people's cognition and behavior.…”
Section: Turning Ideas Into Actionmentioning
confidence: 99%
See 3 more Smart Citations
“…Against this ethical dilemma, a reconciling and reuniting worldview is needed. Toward this end, I humbly propose the Tawhidi (unitive) worldview explicated in my recent work on Islamic mysticism (Alkatiri 2021a). 6 It is a set of assumptions about the world that have powerful effects on people's cognition and behavior.…”
Section: Turning Ideas Into Actionmentioning
confidence: 99%
“…Schumacher found that 'materiality' has been the spirit of development, as explicitly stated in a British Government White Paper on Overseas Development: "To do what lies within our power to help the developing countries to provide their people with the material opportunities for using their talents, or living a full and happy life and steadily improving their lot" (Schumacher 1973: 173). I have argued elsewhere that a belief in 'infinite material progress' has discommodious relations with Darwin's theory of evolution and the secularization of Christianity's doctrine of incarnation (Alkatiri 2021a). When the Global South achieved its independence from European rulers, that belief in progress congealed into what is called 'development ideology'.…”
Section: Materials Civilizationmentioning
confidence: 99%
See 2 more Smart Citations